2013
DOI: 10.1111/hae.12290
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia Joint Health Score in healthy adults playing sports

Abstract: To evaluate outcome of prophylactic clotting factor replacement in children with haemophilia, the Haemophilia Joint Health Score (HJHS) was developed aiming at scoring early joint changes in children aged 4-18. The HJHS has been used for adults on long-term prophylaxis but interpretation of small changes remains difficult. Some changes in these patients may be due to sports-related injuries. Evaluation of HJHS score in healthy adults playing sports could improve the interpretation of this score in haemophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 20 publications
4
40
1
1
Order By: Relevance
“…The Hemophilia Joint Health Score (HJHS), which was recently developed by a consensus of experts, is sensitive to early changes such as mild stage arthropathy [17]. Although originally created for the paediatric population, it has been used in adults, although this use has not been validated [1820]. The HJHS has demonstrated excellent inter-rater and intra-rater reliability, even in inexperienced assessors in a country with limited access to haemophilia services [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The Hemophilia Joint Health Score (HJHS), which was recently developed by a consensus of experts, is sensitive to early changes such as mild stage arthropathy [17]. Although originally created for the paediatric population, it has been used in adults, although this use has not been validated [1820]. The HJHS has demonstrated excellent inter-rater and intra-rater reliability, even in inexperienced assessors in a country with limited access to haemophilia services [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Cut‐off points for clinical relevant changes were ≥|4| for the HJHS‐total score and ≥|2| on joint level. Cut‐off points were based on expert opinion (KF, MT) and a published range of 0‐3 points on the HJHS‐total score in young adults without haemophilia . Differences in HJHS‐total scores between T0 and T1 were tested by the non‐parametric Wilcoxon signed‐rank test.…”
Section: Methodsmentioning
confidence: 99%
“…It is unlikely that joint bleeding caused by competitive sports explains our findings. Sluiter et al evaluated 120 joints in 30 healthy adult men with frequent sports participation (≥4 times a week), and found no instances of abnormal IPSG MRI scores [5]. Similarly, Di Minno et al reported normal joint findings utilizing both ultrasound and MRI in their normal healthy volunteers [6].…”
mentioning
confidence: 99%